Antiretroviral activity and pharmacokinetics in mice of oral bis(pivaloyloxymethyl)-9-(2-phosphonylmethoxyethyl)adenine, the bis(pivaloyloxymethyl) ester prodrug of 9-(2-phosphonylmethoxyethyl)adenine. - Naesens, L (1996)
Lipophilic ester prodrugs of 9-(2-phosphonylmethoxyethyl)adenine (PMEA), i.e., bis(pivaloyloxymethyl)-PMEA [bis(POM)-PMEA] and diphenyl-PMEA, have been synthesized in an attempt to increase the oral bioavailability of this broad-spectrum antiviral agent. The antiretroviral efficacy was determined in severe combined immune deficiency (SCID) mice infected with Moloney murine sarcoma virus (MSV). They were treated twice daily for 5 days after infection. Oral treatment with bis(POM)-PMEA at a dose equivalent to 100 or 50 mg of PMEA per kg of body weight per day proved markedly effective in delaying MSV-induced tumor formation and death of the mice. Oral bis(POM)-PMEA afforded anti-MSV efficacy equal to that of subcutaneous PMEA given at equimolar doses. Oral treatment with PMEA or diphenyl-PMEA proved less efficient. Similarly, in mice infected with Friend leukemia virus (FLV), oral treatment with bis(POM)-PMEA at a dose equivalent to 100 or 50 mg of PMEA per kg per day effected a marked inhibition of FLV-induced splenomegaly (87 and 48% inhibition, respectively), the efficacy being equal to that of PMEA given subcutaneously at equivalent doses. Pharmacokinetic experiments with mice showed that the oral bioavailabilities of PMEA following oral gavage of bis(POM)-PMEA, diphenyl-PMEA, or PMEA (at a dose equivalent to 50 mg of PMEA per kg) were 53,3, and 16%, respectively. These data were calculated from the levels of free PMEA in plasma. Also, the recoveries of free PMEA in the urine upon oral administration of bis(POM)-PMEA, diphenyl-PMEA, or PMEA (at a dose equivalent to 25 mg of PMEA per kg) were 48, 4, and 7%, respectively. Oral bis(POM)-PMEA was not recovered from plasma, suggesting that it was readily cleaved to free PMEA. In contrast, diphenyl-PMEA was not efficiently cleaved to free PMEA, resulting in a rather low oral bioavailability of PMEA from this prodrug. Bis(POM)-PMEA appears to be an efficient oral prodrug of PMEA that deserves further clinical evaluation in human immunodeficiency virus-infected individuals.